PROSEDUR PEMERIKSAAN MSCT ANGIOGRAFI KEPALA DENGAN KLINIS STROKE - Karina Widya Armelia; Jeffri Ardiyanto; Andrey Nino Kurniawan (Perhimpunan Radiografer Indonesia (PARI), 2019)
Background : Reconstruction used to showing the patology of stroke is MPR (Multi Planar Reconstruction). Procedure reformat and filming of MSCT Angiography examination with the clinical of stroke in Radiology Hospital Dr. Moewardi just used 3D MIP, but there was dissatisfaction with the radiologist, so the radiologist do additional reformat independently. The purpose of this study was to explain the procedure of head angiography with MSCT examination in case of stroke to know the reason for head Angiography scanning and to know the reason for using reformat and filming just in 3D MIP. Methods : The type of research used a qualitative researchwith case study appoarch. The data were collected from March to April at Radiologi Hospital Dr. Moewardi by observation, interview with radiology technologist, radiologost and referring physician, and also documentation. Data were analyzed by using interactive model. Results : The result of the research shows that the procedure of Head Angiography examination with MSCT in stroke cases is done by the area from mandibula to vertex. Injection contrast media 370 mg/mL in intra vena with 90 mL and ringer laktat 30 mL. The examination began with scanning of the scanogram, pre contrast, and post contrast. Reformat and filming just in 3D MIP with AP projection, lateral, right oblique and left oblique several in positive and negative. Conclusion : The reason reformat and filming just in 3D MIP because it has revealed vascularization from various angles to be evaluated and the results obtained look like a picture of Digital Substraction Angiography (DSA), making it easier for the referring physician to carry out further examination of coiling with the DSA method.